1992
DOI: 10.1136/bjo.76.6.358
|View full text |Cite
|
Sign up to set email alerts
|

Microwave plaque thermoradiotherapy for choroidal melanoma.

Abstract: Microwave thermoradiotherapy was used as a primary treatment for 44 patients with choroidal melanoma. An episcleral dishshaped microwave antenna was placed beneath the tumour at the time of plaque brachytherapy. While temperatures were measured at the sclera, the tumour's apex was targeted to receive a minimum of 42°C for 45 minutes. In addition, the patients received full or reduced doses of plaque radiotherapy. No patients have been lost to foliow-up. Two eyes have been enucleated: one for rubeotic glaucoma,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

1993
1993
2003
2003

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…There was also an expectation that a reduced radiation dose in patients receiving episcleral thermoradiotherapy may decrease the incidence of treatment complications (4,12,17,18). It has been shown that a reduction of the episcleral radiation dose, if used concurrently with HT, can account for cessation of tumor growth or shrinkage in up to 90% of cases (4,12,17). Decreased incidence of treatment complications in these patients has also been reported (4,12,17).…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…There was also an expectation that a reduced radiation dose in patients receiving episcleral thermoradiotherapy may decrease the incidence of treatment complications (4,12,17,18). It has been shown that a reduction of the episcleral radiation dose, if used concurrently with HT, can account for cessation of tumor growth or shrinkage in up to 90% of cases (4,12,17). Decreased incidence of treatment complications in these patients has also been reported (4,12,17).…”
Section: Introductionmentioning
confidence: 86%
“…These findings provided a rationale to reduce the radiation dose for patients who receive EPRT in addition to episcleral HT. There was also an expectation that a reduced radiation dose in patients receiving episcleral thermoradiotherapy may decrease the incidence of treatment complications (4,12,17,18). It has been shown that a reduction of the episcleral radiation dose, if used concurrently with HT, can account for cessation of tumor growth or shrinkage in up to 90% of cases (4,12,17).…”
Section: Introductionmentioning
confidence: 96%
“…The ultimate goal will be to use the sensitizing effect of radiation as well as the primary cytocidal effects of hyperthermia in order to expect a more efficient form of tumor destruction in choroidal melanomas [85]. There are some Phase I/II clinical trials addressing this question [83,84,86].…”
Section: Radiotherapymentioning
confidence: 99%
“…Hyperthermic treatment consists of scleral temperatures of 42-52°C for a period of 45 min once per patient. Preliminary results indicate that lowering the total radiation dose and additional heat may have the same local control as full-dose radiation treatment [83], but the two major groups [83][84][85] declare thermoradiotherapy for intraocular tumors as empirical and experimental treatment, with clinical indications being in the beginning. This is mainly due to inadequacies of hyperthermia technology in this very special clinical approach.…”
Section: Radiotherapymentioning
confidence: 99%
See 1 more Smart Citation